If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -2) = 16 Reorder the terms: 6(-2 + 4x) = 16 (-2 * 6 + 4x * 6) = 16 (-12 + 24x) = 16 Solving -12 + 24x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 24x = 16 + 12 Combine like terms: -12 + 12 = 0 0 + 24x = 16 + 12 24x = 16 + 12 Combine like terms: 16 + 12 = 28 24x = 28 Divide each side by '24'. x = 1.166666667 Simplifying x = 1.166666667
| 6z-3+z=-2+5z-9 | | x/x-2+4+2x/x^2-4 | | 4-3x=-4 | | 2c+2^1/2c=54 | | 3(2x+1)=75 | | 120x^3-60x^2-180x=0 | | 5x^2=108 | | 9+13y=48 | | 0.03+4=0.07x-20 | | 2c+21/2c=54 | | 23x=5-2x | | 1/3(3x-1)=-1/10-3/10 | | X/4/5=7 | | 5x+19=44 | | 200=0.5x-150 | | 1/3(3x+9)-5+4 | | a^2=-42-13a | | v^2=36 | | x(3x-6)=18 | | z^2=9 | | 3/4/12 | | 6y-3x=18forx | | 12/(3/4) | | (4t^2-t-5)(2t^2+4t-1)= | | 12/3/4 | | 9-2(4*-4+5)= | | x^2+2x-15=33 | | 7x-4=-6 | | 28x^2-85x+63=0 | | 4j+8=32 | | 120=5s | | (x^2+2x-3)/(x+1)^2 |